2011
DOI: 10.1007/s00044-011-9618-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on antitumor activity of metal-based diketone complexes

Abstract: The biological activity of diketone complexes-M(acac) (Acac = MeCOCHCOMe, M = Mo 6? , and Co 2? ) in potential antitumor application was evaluated. The cancer cell lines SMMC-7721 (liver cancer) and SK-OV-3 (ovary cancer) were tested for their viabilities by the MTT method in vitro, which showed that the two compounds exhibited a significant activity against two cell lines. Co(acac) 2 exhibited higher antitumor activity than MoO 2 (acac) 2 did, which is attributed to the fact that Co(acac) 2 could interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Therefore, we synthesized β-diketone-cobalt complexes [Co(acac)2(H 2 O)2, CoAc2]. It has been reported that CoAc2 has cytotoxic effects on liver cancer, ovarian cancer, glioma, and other tumor cells [23,24]. CoAc2 can inhibit DNA synthesis in tumor cells and induce S-phase arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we synthesized β-diketone-cobalt complexes [Co(acac)2(H 2 O)2, CoAc2]. It has been reported that CoAc2 has cytotoxic effects on liver cancer, ovarian cancer, glioma, and other tumor cells [23,24]. CoAc2 can inhibit DNA synthesis in tumor cells and induce S-phase arrest.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Also, of particular interest are discovered antitumor properties of cobalt(II) acetylacetonate and its derivatives. 4 These complexes more effectively inhibit growth of glioma cells compared to the well-known cytostatic fluorouracil. 5 Obviously, cobalt(II) acetylacetonate has a high application potential.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cobalt­(II) acetylacetonate has been widely used in macromolecular engineering. This is due to the fact that it is a highly effective mediator in the controlled radical polymerization of vinyl monomers. Also, of particular interest are discovered antitumor properties of cobalt­(II) acetylacetonate and its derivatives . These complexes more effectively inhibit growth of glioma cells compared to the well-known cytostatic fluorouracil .…”
Section: Introductionmentioning
confidence: 99%
“…β-diketone-cobalt complexes have been shown to suppress SMMC-7721 and SK-OV-3 tumor cell viability and interact with λ-DN (6); however, the molecular mechanisms of β-diketone-cobalt complexes against tumors remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…β-diketone-cobalt complexes are polyoxometalates containing cobalt and traditional methods have been modified for the synthesis ( 5 ). β-diketone-cobalt complexes have been shown to suppress SMMC-7721 and SK-OV-3 tumor cell viability and interact with λ-DN ( 6 ); however, the molecular mechanisms of β-diketone-cobalt complexes against tumors remain unclear.…”
Section: Introductionmentioning
confidence: 99%